2021
DOI: 10.1002/prot.26082
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and structural properties of ATP‐dependent caprolactamase from Pseudomonas jessenii

Abstract: Caprolactamase is the first enzyme in the caprolactam degradation pathway of Pseudomonas jessenii. It is composed of two subunits (CapA and CapB) and sequence‐related to other ATP‐dependent enzymes involved in lactam hydrolysis, like 5‐oxoprolinases and hydantoinases. Low sequence similarity also exists with ATP‐dependent acetone‐ and acetophenone carboxylases. The caprolactamase was produced in Escherichia coli, isolated by His‐tag affinity chromatography, and subjected to functional and structural studies. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 83 publications
(193 reference statements)
0
15
0
Order By: Relevance
“…The MSMEI_3879 locus encodes a 446 amino acid product with homology to ATP-hydrolyzing hydantoinase/oxoprolinase enzymes, which catalyze ring-opening reactions on lactam substrates (7678). Orthologs with >90% sequence identity to MSMEI_3879 are present in members of the genus Mycolicibacterium , but absent in other groups of the family Mycobacteriaceae , including M. tuberculosis (79).…”
Section: Resultsmentioning
confidence: 99%
“…The MSMEI_3879 locus encodes a 446 amino acid product with homology to ATP-hydrolyzing hydantoinase/oxoprolinase enzymes, which catalyze ring-opening reactions on lactam substrates (7678). Orthologs with >90% sequence identity to MSMEI_3879 are present in members of the genus Mycolicibacterium , but absent in other groups of the family Mycobacteriaceae , including M. tuberculosis (79).…”
Section: Resultsmentioning
confidence: 99%
“…The heterologous over-expression of both proteins carrying a N-terminal His-tag in E. coli BL21 (DE3) in lysogeny Fig. 1 State-of-the art in the biohydrolysis of lactams and lactam-like compounds: (A) cyclic amide-bond containing substrates cleaved by hydrolytic enzymes; 7,15,16 (B) ATP-dependent hydrolysis of ε-caprolactam by PjCapAB; 18,19 (C) hydrolysis of oxoproline by ATP-dependent oxoprolinase. 20 broth under isopropyl β-D-1-thiogalactopyranoside (IPTG) induction at 30 °C resulted in poor soluble expression, as was the case in trials at lower temperatures (20 °C, data not shown), despite good overall over-expression (see ESI, Fig.…”
Section: Individual Access To Ppopla and Ppoplb And Activity Assaysmentioning
confidence: 99%
“…Since the presence of bicarbonate was found necessary for the formation of the product, and highest velocity was obtained in the presence of a large excess of bicarbonate (50 mM), bicarbonate was postulated to be involved in the reaction mechanism through the formation of a carboxyphosphate intermediate from ATP. 19 This hypothesis was derived from analogy with related enzymes acetone and acetophenone carboxylases. ATPdependent phosphorylation of bicarbonate is indeed a vital process in a number of biological processes, through which carboxyphosphate can transfer the carboxy group to a variety of acceptors, including acetone and acetophenone, 21,22 or ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…BS4, were described as capable of caprolactam degradation 56,[68][69][70] . Among these organisms, only the enzyme acting upon the cleavage of caprolactam in Pseudomonas jessenii GO3 was described 56,71 . This caprolactamase, which consists of two subunits with high sequence identity to 5-oxoprolinases, hydrolyzes caprolactam into 6-aminohexanoic acid in an ATP-dependent manner 56,71 .…”
Section: Identification Of Candidate Genes Involved In Aca Mineraliza...mentioning
confidence: 99%
“…Among these organisms, only the enzyme acting upon the cleavage of caprolactam in Pseudomonas jessenii GO3 was described 56,71 . This caprolactamase, which consists of two subunits with high sequence identity to 5-oxoprolinases, hydrolyzes caprolactam into 6-aminohexanoic acid in an ATP-dependent manner 56,71 . Such information suggested the possible involvement of the GMOLON4_3203 and GMOLON4_3204 gene products in the breakdown of caprolactam by strain ON4 T .…”
Section: Identification Of Candidate Genes Involved In Aca Mineraliza...mentioning
confidence: 99%